الجزائر سنة1880، من خلال كتاب البلجيكي جيل لوكليرك"من ماكادور إلى بسكرة - قعر المثر نعيم (University Of Eloued جامعة الوادي, 2024)
تتناول هذه الورقة رصدا وتحليلا ثقافيا للتحولات السوسيو ثقافية والجغرافية في الجزائر خلال فترة 1880من خلال كتاب "من ماكادور إلى بسكرة" للكاتب البلجيكي "جيل لوكليرك"، حيث تأتي هذه المداخلة لتحاول فهم قراءة الآخر للأنا التي تمثل الفضاء الجزائري الجغرافي والتاريخي والثقافي وكذا الاجتماعي. تحاول هذه المداخلة طرح أسئلة تمثلت في: ماهي الخصوصيات الثقافية التي تطبع كل مكان جغرافي ممثلة في (تلمسان، القبائل، بسكرة) وماهي مضمرات اللغة التي استعملها الكاتب في وصفه لهاته الأفضية؟ ماهي التفاصيل الإنسانية المختلفة التي انتبه لها الكاتب في هذه الرحلة وما تأثيرها في ذاته الكاتبة والسائحة سلبا وإيجابا؟ This paper provides a cultural observation and analysis of the socio-cultural and geographical changes in Algeria during the 1880s through the book "From Mascara to Biskra" by the Belgian author Gill Loeckx. The aim of this discussion is to explore how others perceive the Algerian geographical, historical, cultural, and social landscape. It seeks to raise questions such as: What are the cultural specificities that characterize each geographical location represented in (Tlemcen, the Kabylie, Biskra), and what linguistic nuances did the author incorporate in describing these spaces? What are the various human details that the author noticed on this journey and their impact on the author's own perception and that of the traveler, both negatively and positively?
In Algeria in 1880, through the book of the Belgian Jules Leclercq "From Macadore to Biskra
Intervention
Keywords: Local; Algeria; image; sacred; trip; المحلي; الجزائر; صورة; المقدس; الرحلة